CORRELATION OF ECONOMIC CONDITION TO EARLY MARRIAGE DECISION - Azkia Nabila; Zahwa Qoblia Andini; Wahyunengsih Wahyunengsih3 (ADIBA : JOURNAL OF EDUCATION, 2022)
The purpose of the study is many correlations of economic level on early marriage that occur in Citepus villages, Subang, West Java. The purpose of the study is to find out how much influence the economy has on making decisions to marry under the age of 19. This study uses data collection through online questions via the Google Questionnaire platform and directly through interview sessions. The data was collected through google from as many as 65 readers, including high school/equivalent students (25 people), students from all majors, and workers (41 people). The results of the study showed that those who live in big cities prefer to continue their education or career rather than having to choose to marry at an early age. Those who have an income below the minimum wage are 26 people with a percentage of 25-50% who have the Medium Correlation criteria. Then some have income above the minimum wage as many as 39 people with a percentage of 50-75% who have the Weak Correlation criteria. Based on the results of research conclusions, the Economic Correlation of Early Marriage often occurs in Indonesia and has even become one of the cultural factors of society.